Physicochemical Properties, Nutritional Composition, and Microbial Profiles of Locally Fermented Yogurt Drink (Lassi) across Three Restaurants in Malaysia (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
This study investigates the nutritional and microbial aspects of locally fermented lassi from three establishments in Seri Kembangan, Selangor. The microbial analysis encompasses Total Plate Count (TPC), Yeast and Mould Count (YMC), Lactic Acid Bacteria (LAB), coliform, Listeria monocytogenes, and Staphylococcus aureus. Additionally, physicochemical properties and nutritional composition, including calcium and sugar identification, viscosity, pH, titratable acidity (TA), whiteness index, Brix, and proximate analysis, were examined. The results indicate heightened levels of coliforms, YMC, and TPC, while notably lacking other pathogenic microorganisms, suggesting potential cleanliness and storage concerns. The LAB count surpasses 107, indicating successful fermentation, supported by low pH and TA levels, aligning with effective LAB concentrations for health benefits. These lassi variants exhibited high sugar content, potentially from the addition of table sugar. Calcium and protein levels suggest a dairy milk base, although variations among establishments hint at unique formulations.
Keywords: Fermented milk; Food establishments; Lactic acid bacteria; Coliform; Staphylococcus aureus